2004
DOI: 10.1002/zaac.200400002
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of BPO4Single Crystals

Abstract: Single crystals of BPO4 were grown by chemical transport reactions with PCl5 using a gradient from 1073 K to 973 K as well as with solvothermal syntheses in the temperature range between 413 K and 523 K using water, ethanol or 2‐propanol as polar protic solvents. The atomic arrangement of BPO4 was reinvestigated by means of single crystal X‐ray diffraction data and confirmed the earlier findings with significantly smaller standard deviations. Thermogravimetric investigations of powdered samples which show no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…16 The MNFE in borophosphate glasses is believed to be due to a non-linear variation of the structural units with composition, which is caused by the high affinity between boron and phosphorous oxide. [17][18][19] Although numerous studies of the structure of borophosphate glasses have been reported, 3,8,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] a quantitative structure-property relation has not been fully established and understood.…”
Section: Introductionmentioning
confidence: 99%
“…16 The MNFE in borophosphate glasses is believed to be due to a non-linear variation of the structural units with composition, which is caused by the high affinity between boron and phosphorous oxide. [17][18][19] Although numerous studies of the structure of borophosphate glasses have been reported, 3,8,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] a quantitative structure-property relation has not been fully established and understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previously it was reported that the homopolymers and copolymers with boron show higher thermal stability than homologous polymers without boron [17]. In addition, boronphosphate (BPO 4 ) was used as an important additive in sulfonated polymers, i.e., SPEEK which contributed positively to the mechanical properties as well as proton conductivity of the polymer electrolyte membranes [18,39]. An interesting feature of BPO 4 is that it retains water up to 300 C [19].…”
Section: Introductionmentioning
confidence: 99%
“…Such a kind of network is encountered in the polymorphs of SiO 2 or in the parent crystal structure of BPO 4 . 20 The first and most prominent example of the isolated tetrahedral pentamer in the solid state is given by [Si-(SiO 4 ) 4 ] 12-, which was discovered in the mineral zunyite 25 The heterocubane-like arrangement of metal cations together with oxygen ( Figure 1b) (Ph ) phenyl, TMU ) N,N,N′,N′-tetramethylurea). 27 The preferred formation of clusters with varying numbers of metal atoms is characteristic for lead 28 32 and Na 0.5 Pb 1.75 GeX 4 (X ) S, Se) 33,34 as examples for chalogenides.…”
mentioning
confidence: 99%